Momentum and calendar effects - Tomasz Wojtowicz (Managerial Economics)
This paper examines the relationship between results of the analysis of the price momentum effect and data mining. Especially, the issue of the day of portfolio formation is considered. The analysis was carried on the basis of daily returns of stocks quoted on Warsaw Stock Exchange in 2003-2010. The evidence indicates that profitability of the momentum strategies can be attributed to the choice of portfolio formation day. It also suggests the connection between mo- mentum and calendar effects.